Farber on film the complete film writings of Manny Farber - Farber, Manny 1917-2008 (Library of America, 2009)
Farber was a unique figure among American movie critics, and long revered by his peers. This volume covers the spectrum from his early and previously uncollected weekly reviews to his brilliant later essays, and defines his enduring significance as writer and thinker.
Includes index
Keywords: Motion pictures / Reviews; Film; Motion pictures -- Reviews; Aufsatzsammlung